Multifactors on Adolescents’ Sexual Behavior - Sriama Muliani; Bq. Safinatunnaja; Nia Supiana; Baiq Tuhu Abdiani; Asri Daniyati (Indonesian Journal of Global Health Research, 2024)
One of the challenges encountered during this period is the feeling of being interested to the opposite gender and being curious about new things. These unhealthy premarital sexual behavior can lead to several effects including STIs, unwanted pregnancies, infections, infertility, child neglect, and early marriage. Related to this matter, this literature review aimed to identify the multifactor related to and affect the adolescents’ sexual behavior. Therefore, researchers aim to identify multifactors that are related to and influence adolescent sexual behavior . This literature study further reviewed 10 articles published in the range of 2014 to 2024, whether it is in google scholar, google pages, google books, book chapters, textbooks, and journals. In this case, the relevant factors affecting the adolescents’ sexual behavior include knowledge, attitude, role of teachers, social environment, media and exposure to pornography, role of parents, as well as role of peers. To overcome these issues, several actions considered able to reduce the tendency of adolescents to engage in sexual behavior prior marriage. These actions include living in a good environment, does not watch pornography, limiting access to media exposing unhealthy sexuality, hanging out with peers with good behavior, having teachers who are able to be role models and provide good supervision and control while in the school environment, and having parents who can provide supervision and affection. Furthermore, it is suggested that all parties, starting from families, schools, and policy makers to formulate an effective method to prevent sexual behavior prior marriage.